2015
DOI: 10.1002/ece3.1735
|View full text |Cite
|
Sign up to set email alerts
|

Evolution along the Great Rift Valley: phenotypic and genetic differentiation of East African white‐eyes (Aves, Zosteropidae)

Abstract: The moist and cool cloud forests of East Africa represent a network of isolated habitats that are separated by dry and warm lowland savannah, offering an opportunity to investigate how strikingly different selective regimes affect species diversification. Here, we used the passerine genus Zosterops (white‐eyes) from this region as our model system. Species of the genus occur in contrasting distribution settings, with geographical mountain isolation driving diversification, and savannah interconnectivity preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…Broad biogeographic breaks are common in many other vertebrate taxa across other parts of sub‐Saharan Africa including ungulates (Arctander, Johansen, & Coutellec‐Vreto, ; Lorenzen et al., ), small mammals (Mynhardt et al. ), birds (Habel et al., ) and reptiles (Tolley et al., ). This points towards the importance of refugia in the persistence of biodiversity during long‐term climate change (Fjeldså & Lovett, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad biogeographic breaks are common in many other vertebrate taxa across other parts of sub‐Saharan Africa including ungulates (Arctander, Johansen, & Coutellec‐Vreto, ; Lorenzen et al., ), small mammals (Mynhardt et al. ), birds (Habel et al., ) and reptiles (Tolley et al., ). This points towards the importance of refugia in the persistence of biodiversity during long‐term climate change (Fjeldså & Lovett, ).…”
Section: Discussionmentioning
confidence: 99%
“…These measures are a useful proxy for historical climatic stability through deeper time (see Sandel et al, 2011) and can help to explain biogeographic breaks and endemism at the species level not only in many amphibians (e.g., Barratt et al, 2017;Loader et al, 2014;Zimkus et al, 2017) but also across other taxonomic groups. Broad biogeographic breaks are common in many other vertebrate taxa across other parts of sub-Saharan Africa including ungulates (Arctander, Johansen, & Coutellec-Vreto, 1999;Lorenzen et al, 2012), small mammals (Mynhardt et al 2015), birds (Habel et al, 2015) and reptiles (Tolley et al, 2011). This points towards the importance of refugia in the persistence of biodiversity during long-term climate change (Fjeldså & Lovett, 1997).…”
Section: Environmental Correlates Of Pementioning
confidence: 99%
“…Habel et al. () observed a significant increase in wing length and body weight with the altitude for this species. This variation has also been documented in other similar avian systems.…”
Section: Discussionmentioning
confidence: 65%
“…Habel et al. () found that wing length and body weight were significantly correlated with altitude and habitat type in the highland species Zosterops poliogaster in East Africa. Habel et al.…”
Section: Discussionmentioning
confidence: 99%
“…), phenotypic (Borghesio and Ndanganga ; Habel et al. ) and bioacoustic differences (Habel et al. ; Husemann et al.…”
Section: Discussionmentioning
confidence: 99%